The Effect of Electronic Guidance Program Using (Lecture Maker) on the Improvement of Academic Achievement Motivation in Soccer for Physical Education and Sport Sciences’ Students - Ali, Ali Abdulnabi; Khalaf, Ali Subhi (Journal of Physical Education, 2021)
The research aimed at identifying the affectivity of self – organization style on improving academic achievement motivation. The researchers applied the research on (225) students of first, third and fourth year college students. Then a self – organization guidance program was constructed with 12 guidance session on physical education and sport sciences’ students who showed a low level of academic study motivation in soccer. The main subject was (20) divided into two equal groups and the results showed that the counseling program has a positive effect on self – organization style on academic studying motivation for physical education and sport sciences’ college students.